Regulation of IL-6 Secretion by Astrocytes via TLR4 in the Fragile X Mouse Model - Krasovska, Victoria; Doering, Laurie C. (Frontiers in Molecular Neuroscience, 2018)
Fragile X syndrome (FXS) is identified by abnormal dendrite morphology and altered synaptic protein expression. Astrocyte secreted factors such as Tenascin C (TNC), may contribute to the synaptic changes, including maturation of the synapse. TNC is a known endogenous ligand of toll-like receptor 4 (TLR4) that has been shown to induce the expression of pro-inflammatory cytokines such as interleukin-6 (IL-6). At the molecular level, elevated IL-6 promotes excitatory synapse formation and increases dendrite spine length. With these molecular changes linked to the phenotype of FXS, we examined the expression and the mechanism of the endogenous TLR4 activator TNC, and its downstream target IL-6 in astrocytes from the FMR1 KO mouse model. Secreted TNC and IL-6 were significantly increased in FMR1 KO astrocytes. Addition of TNC and lipopolysaccharide (LPS) induced IL-6 secretion, whereas the antagonist of TLR4 (LPS-RS) had an opposing effect. Cortical protein expression of TNC and IL-6 were also significantly elevated in the postnatal FMR1 KO mouse. In addition, there was an increase in the number of VGLUT1/PSD95 positive synaptic puncta of both WT and FMR1 KO neurons when plated with astrocyte conditioned media from FMR1 KO astrocytes, compared to those plated with media from wild type astrocytes. By assessing the cellular mechanisms involved, a novel therapeutic option could be made available to target abnormalities of synaptic function seen in FXS.